Simultaneous Detection of Ebola Virus and Pathogens Associated With Hemorrhagic Fever by an Oligonucleotide Microarray - Yao, Wenwu; Yang, Zhangnv; Lou, Xiuyu; Mao, Haiyan; Yan, Hao; Zhang, Yanjun (Frontiers in Microbiology, 2021)
Ebola virus infection causes severe hemorrhagic fever and its mortality rates varied from 25% to 90% in the past outbreaks. The highly infectious and lethal nature of this virus highlights the need for reliable and sensitive diagnostic methods to distinguish it from other diseases that can cause similar clinical symptoms. Based on multiplex polymerase chain reaction (PCR) and oligonucleotide microarray technology, a cost-effective, multi-pathogen and high-throughput method was developed for the simultaneous detection of Ebola virus and other pathogens associated with hemorrhagic fever, including Marburg virus, Lassa fever virus, Junin virus, Machupo virus, Rift Valley fever virus, Crimean-Congo hemorrhagic fever virus, malaria parasite, Hantavirus, Severe fever with thrombocytopenia syndrome virus, Dengue virus, Yellow fever virus, Chikungunya virus, Influenza A virus, and Influenza B virus. This assay conferred an excellent specificity for target pathogens, without cross signal between the probes. The limit of detection was 103 copies/μL approximately. A total of 60 positive samples with nucleic acid of different pathogens were detected, a concordance of 100% was observed between our microarray and Real-Time PCR. Consequently, the described oligonucleotide microarray may translate into a specific and sensitive assay for diagnosis and surveillance of infections caused by Ebola virus and other species of hemorrhagic fever pathogens.